State of Charge Balancing Analysis Using Droop Control on Energy Storage System - Muhammad Cahyo Bagaskoro; Aripriharta; Muhammad Afnan Habibi; Gabrielley Ferdhiansyah Riyadi (LPPM Universitas Negeri Semarang, 2024)
The growing energy crisis has driven the global shift toward renewable energy development. Governments are taking significant steps by promoting diverse sources such as photovoltaic (PV), wind turbines, and battery systems. Among these, Battery Energy Storage Systems (BESS) play a crucial role in decentralized energy generation, especially in DC microgrids. Within BESS, Battery Energy Storage Units (BESUs) are vital components, where monitoring the State of Charge (SOC) is essential. The Coulomb Counter (CC) method is widely used due to its reliability in SOC estimation. This study introduces a dynamic SOC balancing strategy using droop control, aiming to maintain uniform SOC across multiple BESUs. The proposed method regulates BESU discharge behaviour to achieve SOC parity and optimize energy distribution throughout the microgrid. Simulations under various operating scenarios charging and discharging modes with different SOC levels were conducted using the MATLAB/SIMULINK® environment. The results show that the control approach effectively equalizes SOC levels under non-uniform initial conditions. The balancing duration varied according to the initial SOC difference, highlighting the controller's adaptability. Although the study did not directly measure battery lifespan or energy efficiency, enhanced SOC uniformity is expected to reduce current imbalances and operating stress, potentially improving long-term system reliability. This research offers valuable insights into the control and management of BESS, supporting the stable integration of renewable energy in modern microgrid applications.